The impact of self-care deficits and infection control among patients with tracheostomies in intensive care unit: A scoping review - Aluh Eka Novianty; Rondhianto Rondhianto; Iis Rachmawati (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Patients in intensive care units (ICUs) with tracheostomies are particularly susceptible to nosocomial infections, notably ventilator-associated pneumonia (VAP) and lower respiratory tract infections. A key contributing factor is the presence of self-care deficits, as these patients are generally unable to maintain airway hygiene or perform tracheostomy wound care independently. These deficits are compounded by healthcare worker workload, constrained ICU resources, and the absence of standardized care protocols. A comprehensive synthesis of existing evidence is therefore necessary to clarify the relationship between self-care deficits and infection risk. Purpose: To explore and analyze the association between self-care deficits and infection incidence in ICU patients with tracheostomy, with a focus on identifying key risk factors, implementation challenges, and effective infection prevention strategies. Method: A systematic literature search was conducted using databases including ProQuest, JSTOR, BMC, and Google Scholar, covering studies published between January 2015 and December 2024. Of 1,157 articles initially identified, 35 were selected for full-text review based on predefined inclusion and exclusion criteria. Quality appraisal was conducted using the Joanna Briggs Institute (JBI) framework, yielding 11 articles for final inclusion. Results: Self-care deficits substantially contribute to nosocomial infection risk in ICU patients with tracheostomies. Identified risk factors include ineffective secretion management, poor oral hygiene, and improper suctioning techniques. Inadequate education for both patients and caregivers following ICU discharge further exacerbates this risk. Additional barriers include limited medical equipment availability, insufficient training in tracheostomy wound care, and healthcare provider burden. Furthermore, there is a lack of research addressing the long-term consequences of self-care deficits and the effectiveness of patient-centered educational interventions. Conclusion: Self-care deficits significantly elevate the risk of infection among ICU patients with tracheostomies, primarily due to impaired hygiene and secretion management. Contributing factors include insufficient resources, absence of standardized protocols, and limited educational support for patients and caregivers. Although nursing interventions have demonstrated potential in mitigating these risks, their implementation remains inconsistent. Further research is warranted to assess the long-term effectiveness of targeted, patient-centered self-care education strategies.